Plano de negócios para a empresa Green Glow - Dantas, Maria Eduarda Félix (2023)
The business plan is an essential tool for undertaking due to its planning nature that allows you to identify the viability of the new business and reduce risks. The general objective of this work is to develop a business plan that enables the implementation of the company Green Glow, an innovative initiative for dry cleaning of cars and motorcycles that intermediates services through an application. The service will be carried out at home in the city of Natal in Rio Grande do Norte. The research method was descriptive and quantitative. The work covered the administrative, marketing, operational, financial and strategic dimensions and through these analyzes and the market research developed, it was possible to prove the viability of the enterprise.